Comparison of cage versus floor rearing systems on broiler performance, welfare and behavioral parameters - Yilmaz Dikmen, B; Gündüz, M (Journal of the Hellenic Veterinary Medical Society, 2025)
This study was carried to determine the effects of the floor type (litter rearing and sledge cage system) on performance, welfare and behaviour parameters of broilers. A total of 240 one-day-old Ross 308 male broilers were reared in two different rearing systems; sledge cage system (CS) and litter floor system (FS) until 42 weeks of age. The final body weight and body weight gain between 1-42 days of age were tend to be higher in FS than CS system (P=0.060). The cumulative feed consumption was similar between the rearing systems at 1-21, 1-28, 1-35 and 1-42 days of age periods (P>0.05). The feed conversion ratio was lower in FS than in CS system (P=0.004). The productivity index was higher in FS than CS system at 1-42 days of age period (P=0.008). The plumage cleanliness score was higher and foot pad dermatitis was lower in FS than in CS (P=0.010 and P=0.0001). The gait score was found similar in both rearing system but numerically lower gait problem was found in FS than CS system (P>0.05). The tonic immobility duration and induction number were found similar in both rearing system (P>0.05). The higher eating, scracthing, wing clap-body shaking, spot pecking; and lesser sleeping behaviour were observed in FS than in CS (P=0.011, P=0.009, P=0.047, P=0.001 and P=0.003; respectively). The drinking, walking, standing and sitting behaviour of broilers were found similar in both rearing system (P>0.05). The wing-leg streching, feather maintanence and pecking each other behaviour of broilers were found similar in both rearing system (P>0.05). The aggressive pecking behaviour was tend to observed more in FS than in CS system (P=0.062). It has been determined that broilers had better performance, welfare and behaviour parameters in the floor-rearing system when the litter condition is good. Keywords: Behaviour; Broiler; Performance; Rearing systems; Welfare